2005
DOI: 10.1124/jpet.104.081539
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of the 4-Aminotetrahydroquinoline Derivatives, Selective Chemoattractant Receptor-Homologous Molecule Expressed on T Helper 2 Cell Antagonists, on Eosinophil Migration Induced by Prostaglandin D2

Abstract: Prostaglandin (PG) D 2 , a major cyclooxygenase metabolite generated from immunologically stimulated mast cells, is known to induce activation and chemotaxis in eosinophils, basophils, and T helper 2 (Th2) lymphocytes via a newly identified PGD 2 receptor, chemoattractant receptor-homologous molecule expressed on Th2 cells (CRTH2). CRTH2 is hypothesized to play an important role in the outcome of allergic responses. However, the absence of selective CRTH2 antagonists has prevented the elucidation of the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…We therefore analyzed antagonist behavior in a more natural ex vivo cell system, using human eosinophils, which endogenously express CRTH2 as a model system. Purified human eosinophils undergo shape change upon exposure to PGD2 that is characterized by a biphasic dose-response curve (Hirai et al, 2001;Bohm et al, 2004); the response is known to be mediated via CRTH2, because it is sensitive to blockade with CRTH2 antagonists (Bohm et al, 2004;Mathiesen et al, 2005;Mimura et al, 2005). Our study confirmed the inhibitive effect of ramatroban, which led to concentration-dependent dextral shifts of the PGD2-mediated shape change responses, consistent with classic competitive antagonism (Fig.…”
Section: The Compounds Preserve Their Pharmacological Profile In Humasupporting
confidence: 76%
“…We therefore analyzed antagonist behavior in a more natural ex vivo cell system, using human eosinophils, which endogenously express CRTH2 as a model system. Purified human eosinophils undergo shape change upon exposure to PGD2 that is characterized by a biphasic dose-response curve (Hirai et al, 2001;Bohm et al, 2004); the response is known to be mediated via CRTH2, because it is sensitive to blockade with CRTH2 antagonists (Bohm et al, 2004;Mathiesen et al, 2005;Mimura et al, 2005). Our study confirmed the inhibitive effect of ramatroban, which led to concentration-dependent dextral shifts of the PGD2-mediated shape change responses, consistent with classic competitive antagonism (Fig.…”
Section: The Compounds Preserve Their Pharmacological Profile In Humasupporting
confidence: 76%
“…This observation has led to the identification of ramatroban analogues, which are potent CRTH2 antagonists devoid of TP activity ( Ulven and Kostenis, 2005 ). The only non‐acid CRTH2 antagonists so far described are 4‐aminotetrahydroquinoline derivatives as exemplified by K117 and K604 ( Mimura et al , 2005 ).…”
Section: Pharmacological Properties Of Dp1 and Crth2mentioning
confidence: 99%
“…Other indolic compounds with selective DP 2 receptor antagonist activities have also recently been reported (Armer et al, 2005;Birkinshaw et al, 2006). A series of tetrahydroquinoline derivatives have also been identified as selective DP 2 antagonists (Mimura et al, 2005).…”
Section: Effects Of 15r-pgdmentioning
confidence: 99%